Literature Review Regarding the Concept of Resilience and its Assessment in the Context of the Economic Dimension - Sergey Lisnyak (CES Working Papers, 2015)
The concept of resilience is rather complicated and deep in content as well as quite complex for an assessment and measurement. This paper aims to make appropriate an literature review and to highlight the definition of “resilience”, as well as to analyze components in the context of the economic dimension, which, on the one hand, allowed seeing the diversity of the processes for economic resilience, and on the other hand contributed to the isolation and understanding of the main basics in the process of its assessment. Content analysis of core Resilience Indices made by international organizations and research institutes as well as fundamental research papers and theories on the issue of resilience has been carried out to identify generals in mainstream of comprehension the definition and approaches to its assessment. According to the results, the analyzed papers and reports raise a systemized collection of definitions and components that suggest the detailed view, for better understanding of approaches to economic resilience assessment.
Keywords: F6; O1; 330; resilience; definition of resilience; economic resilience; systematic literature review